GERAKAN INDONESIA TANPA PACARAN (ITP): DARI RESEPSI AL-QUR’AN DAN HADIS HINGGA KONSTRUKSI SOSIAL - Fatmawati, Fatimah (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
This study aims to analyze Indonesia Tanpa Pacaran (ITP) movement in the perspective of the reception of the Qur'an and Hadith and Social Construction by Berger and Luckman's. This study answers three questions: First, how the concept of ITP movement. Second, how reception of the Qur'an and Hadith in this Movement. Third, how social construction of this movement. As a social movement, ITP has five important elements. These elements are people and participants, goals and agendas, and targets. Meanwhile, in the perspective of social construction, a social reality have three moments of externalization-objectivation-internalization who occurs simultaneously. The verse “prohibit of zina” and the hadith about “ikhtilat” were accepted by La Ode as a prohibition on dating. The dialectic between text and the reality (La Ode thinks that dating causes negative effects to Muslim generation) has led to establish Indonesia Tanpa Pacaran movement. This idea was externalized to the community on September 7, 2015. After the ITP movement manifested itself in the reality of society, gradually the movement gets legitimacy. His social media accounts are followed by millions of people. This process is known as objectivation. Furthermore, their campaigns on social media periodically, about the effects of dating, are internalized by the members and their sympathizers. This internalization then forms anti-dating behavior in society.